Effects of Academic Departments on Students' Approaches to Studying - Ramsden, Paul; Entwistle, Noel J. (British Journal of Educational Psychology, 1981)
Summary. 2208 students from 66 academic departments in six contrasting disciplines from British universities and polytechnics completed an ‘approaches to studying’ inventory and a course perceptions questionnaire. Factor analyses of these instruments confirmed the factor structures previously reported. Approaches to studying can be described in terms of three main factors—orientations towards personal meaning, reproducing, and achieving. In the present analysis the final factor split into two: achieving orientation and a factor labelled ‘disorganised and dilatory’ which showed a close relationship with self-rating of academic progress. The course perceptions questionnaire produced two main factors. One described formal teaching methods, vocational relevance, and clear goals and standards, and the other represented a favourable departmental evaluation with the highest loadings on good teaching and openness to students. Subsequent analyses examined links between students' perceptions of their main academic departments and their reported approaches to studying. Departments with highest mean scores on meaning orientation were perceived as having good teaching and allowing freedom in learning. Departments with the highest mean scores on reproducing orientation were seen to have a heavy workload and a lack of freedom in learning. The implications of these statistical findings are discussed in relation to continuing analyses of interview data which clarify the ways in which the organisation of teaching and courses may affect students' approaches to learning.